Increased invasion of ED-1 positive macrophages in both ipsi- and contralateral dorsal root ganglia following unilateral nerve injuries - Dubový, P; Tucková, L; Jancálek, R; Svízenská, I; Klusáková, I (Neuroscience letters, 2007)
There is an increasing evidence that unilateral nerve injury induces cellular and molecular changes in the associated DRG not only on the ipsilateral but also in the contralateral side. In this investigation, ED-1+ macrophages were quantified by image analysis in the naïve L5 DRG (nDRG) and compared with the ipsi- and contralateral ones 2 and 4 weeks after unilateral sciatic nerve ligature and ventral root transection (VRT). A few ED-1+ macrophages were found in nDRG but not closely associated with the neuronal bodies. In contrast, following nerve injuries ED-1+ macrophages and their processes were frequently located close neuronal bodies and became their satellite cells. Moreover, an increased number of ED-1+ cells was found in the ipsilateral DRG 2 weeks after unilateral sciatic nerve ligature or VRT, but no significant differences were measured between 2 and 4 weeks after both types of nerve lesion. Contralateral DRG displayed a significant enhanced number of ED-1+ cells no sooner than 4 weeks from sciatic nerve ligature. In contrast, VRT induced a significant increased invasion of the ED-1+ cells in the contralateral DRG as early as 2 weeks after operation. Our experiments indicate that a significantly higher number of ED-1+ macrophages remained in both ipsi- and contralateral DRG up to 4 weeks from nerve injury. Based on results from different models of nerve injury, we suggest that more than one mechanism operates to stimulate the invasion of ED-1+ macrophages into the DRG including retrograde transport of factors produced during Wallerian degeneration or their delivery by blood flow. Signaling for macrophage invasion into DRG contralateral to nerve injury may be mediated by lost motoneurons or by interneurones.
Keywords: Motor Neurons; Interneurons; modely nemocí na zvířatech; biologické markery; Rats, Wistar; Biomarkers; spinální ganglia; Neuralgia; nervus ischiadicus; imunohistochemie; Sciatic Nerve; potkani Wistar; interneurony; krysa rodu Rattus; Animals; ženské pohlaví; Immunohistochemistry; zvířata; makrofágy; Functional Laterality; Rats; Disease Models, Animal; motorické neurony; Ganglia, Spinal; Female; Macrophages; funkční lateralita; neuralgie